Biomedia - Thacker, Eugene (Electronic mediations, 2004)
Annotation As biotechnology defines the new millennium, genetic codes and computer codes increasingly merge-life understood as data, flesh rendered programmable. Where this trend will take us, and what it might mean, is what concerns Eugene Thacker in this timely book, a penetrating look into the intersection of molecular biology and computer science in our day and its likely ramifications for the future. Integrating approaches from science and media studies, Biomedia is a critical analysis of research fields that explore relationships between biologies and technologies, between genetic and computer "codes." In doing so, the book looks beyond the familiar examples of cloning, genetic engineering, and gene therapy-fields based on the centrality of DNA or genes-to emerging fields in which "life" is often understood as "information." Focusing especially on interactions between genetic and computer codes, or between "life" and "information," Thacker shows how each kind of "body" produced-from biochip to DNA computer-demonstrates how molecular biology and computer science are interwoven to provide unique means of understanding and controlling living matter. Throughout, Thacker provides in-depth accounts of theoretical issues implicit in biotechnical artifacts-issues that arise in the fields of bioinformatics, proteomics, systems biology, and biocomputing. Research in biotechnology, Biomedia suggests, flouts our assumptions about the division between biological and technological systems. New ways of thinking about this division are needed if we are to understand the cultural, social, and philosophical dimensions of such research, and this book marks a significant advance in the coming intellectualrevolution. Eugene Thacker is assistant professor of new media in the School of Literature, Communication, and Culture at the Georgia Institute of Technology. His writings on the social and cultural aspects of biotechnology.